(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
One of the most dynamically developing branches of active tourism in Europe in recent decades has been sports tourism, which includes snow sports. Although due to the geographical conditions of Hungary, the availability of domestic winter centres satisfying the needs of those who like snow sports is limited, the number of consumers exceeds half a million. A significant number of Hungarian skiers and snowboarders regularly visit the winter centres of the surrounding countries. The vast majority of snow sports consumers do this as a leisure activity. There are significant differences in their level of education and knowledge. In our study, based on a non-representative survey conducted in the winter of 2020, we want to examine the prequalification, sports education habits, satisfaction and level of knowledge of Hungarian consumers engaged in snow sports, based on their own judgment.